Diabetes mellitus and adverse outcomes after carotid endarterectomy: A systematic review and meta-analysis - Li, Fengshi; Zhang, Rui; Di, Xiao; Niu, Shuai; Rong, Zhihua; Liu, Changwei; Ni, Leng (Chinese medical journal, 2023)
There is still uncertainty regarding whether diabetes mellitus (DM) can adversely affect patients undergoing carotid endarterectomy (CEA) for carotid stenosis. The aim of the study was to assess the adverse impact of DM on patients with carotid stenosis treated by CEA. Eligible studies published between 1 January 2000 and 30 March 2023 were selected from the PubMed, EMBASE, Web of Science, CENTRAL, and ClinicalTrials databases. The short-term and long-term outcomes of major adverse events (MAEs), death, stroke, the composite outcomes of death/stroke, and myocardial infarction (MI) were collected to calculate the pooled effect sizes (ESs), 95% confidence intervals (CIs), and prevalence of adverse outcomes. Subgroup analysis by asymptomatic/symptomatic carotid stenosis and insulin/noninsulin-dependent DM was performed. A total of 19 studies (n = 122,003) were included. Regarding the short-term outcomes, DM was associated with increased risks of MAEs (ES = 1.52, 95% CI: [1.15-2.01], prevalence = 5.1%), death/stroke (ES = 1.61, 95% CI: [1.13-2.28], prevalence = 2.3%), stroke (ES = 1.55, 95% CI: [1.16-1.55], prevalence = 3.5%), death (ES = 1.70, 95% CI: [1.25-2.31], prevalence =1.2%), and MI (ES = 1.52, 95% CI: [1.15-2.01], prevalence = 1.4%). DM was associated with increased risks of long-term MAEs (ES = 1.24, 95% CI: [1.04-1.49], prevalence = 12.2%). In the subgroup analysis, DM was associated with an increased risk of short-term MAEs, death/stroke, stroke, and MI in asymptomatic patients undergoing CEA and with only short-term MAEs in the symptomatic patients. Both insulin- and noninsulin-dependent DM patients had an increased risk of short-term and long-term MAEs, and insulin-dependent DM was also associated with the short-term risk of death/stroke, death, and MI. In patients with carotid stenosis treated by CEA, DM is associated with short-term and long-term MAEs. DM may have a greater impact on adverse outcomes in asymptomatic patients after CEA. Insulin-dependent DM may have a more significant impact on post-CEA adverse outcomes than noninsulin-dependent DM. Whether DM management could reduce the risk of adverse outcomes after CEA requires further investigation.